PHARM-IIDEx 2023 / Dr. Siti Syairah Mohd Mutalip and Associate Prof. Dr. Mahmathi Karuppannan - Mohd Mutalip, Siti Syairah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
The Faculty of Pharmacy successfully organized the Pharmacy Invention, Innovation, and Design Exhibition 2023 (Pharm-IIDEx 2023) from 1st June – 16th August 2023. Carrying the theme ‘Empowered by Innovation’, this event has attracted more than 60 national and international teams. The event was conducted in two modes – the physical and virtual platforms, to allow participants to present their inventions and innovations in the field related to health and well-being; including pharmacy, health sciences, medicine, cosmetics, nutraceuticals, agrotechnology, and biotechnology. The competition involved four different categories of participation. The first category is for Academician and Postgraduate students, the second category is for Non-Academician and Researchers from Universities/Research Agencies, the third category is for Undergraduate students and the fourth category is for Primary and Secondary School students.